Association Between Physical Activity, Screen Time and Sleep, and School Readiness in Canadian Children Aged 4 to 6 Years. Issue 2 (February 2022) - Vanderloo, Leigh M.; Omand, Jessica; Keown-Stoneman, Charles D. G.; Janus, Magdalena; Tremblay, Mark S.; Maguire, Jonathon L.; Borkhoff, Cornelia M.; Lebovic, Gerald; Parkin, Patricia; Mamdani, Muhammad; Simpson, Janis Randall; Duku, Eric; et al.
Abstract: Objective: School readiness is strongly associated with a child's future school success and well-being. The primary objective of this study was to determine whether meeting 24-hour movement guidelines (national physical activity, sedentary behaviors, and sleep recommendations) was associated with school readiness measured with mean scores in each of the 5 developmental domains of the Early Development Instrument (EDI) in Canadian children aged 4 to 6 years. Secondary objectives include examining the following: (1) the association between meeting 24-hour movement guidelines and overall vulnerability in school readiness and (2) the association between meeting individual physical activity, screen use and sleep recommendations, and overall school readiness. Methods: A prospective cohort study was performed using data from children (aged 4–6 years) who participated in a large-scale primary care practice-based research network. Results: Of the 739 participants (aged 5.9 + 0.12 years) in this prospective cohort study, 18.2% met the 24-Hour Movement Guidelines. Linear regression models (adjusted for child/family demographic characteristics, number of siblings, immigration status, and annual household income) revealed no evidence of an association between meeting all 24-hour movement guidelines and any of the 5 domains of the EDI ( p > 0.05). Adjusted linear regression models revealed evidence of an association between meeting screen use guidelines and the "language and cognitive development" (β = 0.16, p = 0.004) domain, and for the sleep guideline, there was a statistically significant association with the "physical health and well-being" (β = 0.23, p = 0.001), the "language and cognitive development" (β = 0.10, p = 0.003), and the "communication skills and general knowledge" (β = 0.18, p < 0.001) domain. Conclusion: Early lifestyle interventions targeting screen use and sleep may be beneficial for improving a child's readiness for school. Abstract : This article has supplementary material on the web site: www.jdbp.org.